2007
DOI: 10.12968/bjon.2007.16.19.27362
|View full text |Cite
|
Sign up to set email alerts
|

Caring for patients with suicidal behaviour: an exploratory study

Abstract: Presentation to the Emergency Department (ED) of patients with suicidal behaviours is relatively common. While many of these patients may be referred on to specialist mental health services, many are either discharged with no psychiatric follow-up or leave before being seen. There is therefore an increasing onus on the staff of Emergency Departments to become involved in the assessment and initial management of this patient group. The aim of this study was to describe the experiences and challenges that nurses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 16 publications
(25 reference statements)
0
32
0
Order By: Relevance
“…In addition to the fear and anger engendered by aggressive or bizarre behaviour (Kerrison & Chapman 2006, Pich et al 2009), staff tension was further increased due to the revolving door nature of many presentations and lack of feedback or apparent follow-up resulted in a sense of hopelessness and a why bother attitude (Anderson et al 2003, Hadfield Emergency Department Attitudes Toward Mental Illness 9 et al , McElroy & Sheppard 1999. One qualitative study reported that staff perceived individuals with mental health presentations to be manipulative (Bergmans et al 2009) whilst another one stated that complaints were often not seen as genuine on initial presentation (Doyle et al 2007). MacKay and Barrowclough (2003) found that the greater the negative affect of staff towards the individual, the less the propensity to help.…”
Section: Staff Perspectivesmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition to the fear and anger engendered by aggressive or bizarre behaviour (Kerrison & Chapman 2006, Pich et al 2009), staff tension was further increased due to the revolving door nature of many presentations and lack of feedback or apparent follow-up resulted in a sense of hopelessness and a why bother attitude (Anderson et al 2003, Hadfield Emergency Department Attitudes Toward Mental Illness 9 et al , McElroy & Sheppard 1999. One qualitative study reported that staff perceived individuals with mental health presentations to be manipulative (Bergmans et al 2009) whilst another one stated that complaints were often not seen as genuine on initial presentation (Doyle et al 2007). MacKay and Barrowclough (2003) found that the greater the negative affect of staff towards the individual, the less the propensity to help.…”
Section: Staff Perspectivesmentioning
confidence: 99%
“…A number of both qualitative and quantitative studies reported that ED staff generally felt ill-prepared to assess and care for individuals with mental health problems (Doyle et al 2007, Friedman et al 2006, Pich et al 2009, Summers & Happell 2003. The three papers, which measured perceived skill level and attitude, all found that those with greater perceived self-efficacy in assessment and treatment had more positive attitudes (Kishi et al 2011, McAllister et al 2001, Wright et al 2003.…”
Section: Staff Perspectivesmentioning
confidence: 99%
See 3 more Smart Citations